Digital adoption, automation, and labor markets in developing and emerging economies - Alan Finkelstein Shapiro; Federico S. Mandelman (Federal Reserve Bank of Atlanta, 2019)
We document a strong negative link between self-employment and the rate of digital adoption by firms in developing and emerging economies. No link between digital adoption and the unemployment rate is found, however. To explain this evidence, we build a general equilibrium search-and-matching model with endogenous labor force participation, self-employment, endogenous firm entry, and information-and-communications technology adoption. The main finding is that changes in the cost of technology adoption per se cannot rationalize the evidence. Instead, changes in firms' barriers to entry directly linked to the cost of technology adoption are key to explain the data.
Keywords: E24; J23; J24; J64; O14; 330; Information-and-telecommunications-technology capital (ICT); digital adoption; automation; labor search frictions; unemployment; self-employment; endogenous firm entry; developing and emerging economies